The psychosocial impact of mobile social networking among young adults in Jamaica: a brief review of the literature. (2016) - Hunter, Shawnna
There are numerous reports on the impact of mobile social networking among emerging adults in several developed countries as well as on the growing use of mobile phones. However, there is limited understanding of this phenomenon and its impact in regions such as the Caribbean. There is evidence in the scholarly literature of inconclusive arguments surrounding the association between psychosocial issues and mobile social networking among young adults. The academic literature is also inconclusive on gender and self-esteem in relation to the underpinning of the use of social networking among emerging adults. Additionally, limited investigations have been reported on this growing phenomenon in specific contexts such as the Caribbean region.